Conceptualization of the Transmission Dynamic of Faecal-Orally Transmitted Diseases in Urban Exposome of Sub-Saharan Africa - Zerbo A; Castro Delgado R; Arcos González P (Dove Medical Press, 2022)
Alexandre Zerbo, Rafael Castro Delgado, Pedro Arcos González Unit of Research in Emergency and Disaster, Department of Medicine, Faculty of Medicine and Health Sciences, University of Oviedo, Oviedo, Asturias, SpainCorrespondence: Alexandre Zerbo, Unit of Research in Emergency and Disaster, Department of Medicine, Faculty of Medicine and Health Sciences, University of Oviedo, Oviedo, Asturias, 33006, Spain, Email crateva@yahoo.frAbstract: In sub-Saharan Africa, many urban dwellers are at risk of faecal-orally transmitted diseases due to unplanned and growing urbanization with inadequate sanitation. Making it essential to understand the urban transmission of these diseases and the associated responses. This perspective paper discussed an approach to design a diagram of transmission dynamic from a combination of an urban exposome framework and transmission of faecal-oral diseases. The result is an exposome diagram displaying the interconnection of exposure components and potential barriers to stop the transmission of faecal-oral diseases in the urban area subdivided into public, domestic and individual. As an exposome diagram, it helps to follow the dynamics of exposure over time and to plan targeted surveillance and intervention.Keywords: faecal oral diseases, transmission dynamic, exposome diagram, urban areas, sub- Saharan Africa